The Imaginary Worlds of ISPOR: Modeled Cost-Effectiveness Claims Published in Value in Health from January 2016 to December 2016 - Paul C Langley; Taeho Greg Rhee (INNOVATIONS in Pharmacy, 2017)
In 2016, a review of modeled cost-effectiveness studies published in Value in Health between January 2015 and December 2015 was presented. The purpose of the review was to consider whether these modeled claims for cost-effectiveness met the standards of normal science: were the claims made credible, evaluable and replicable? The review concluded that none of the 16 studies assessed met this standard. They should be seen as thought experiments; the construction of imaginary worlds which should be categorized as pseudoscience. The reader, or health care decision maker, would have had no idea, and would never know, whether the claims were right, wrong or misleading. Similar reviews were undertaken in Pharmacoeconomics and the Journal of Medical Economics and came to the same conclusion. The purpose of this second review is to consider the modeled claims published in Value in Health between January 2016 and December 2016, applying the same criteria. Unfortunately, for those who subscribe to the standards of normal science, we must come to the same conclusion. Of the 13 economic evaluations reviewed, 12 simulated claims that were immune to failure. The model structures ensured that the claims were neither evaluable nor replicable. They were categorized as pseudoscience; they failed to meet the standards of normal science. Five of these studies were supported by manufacturers and all supported the manufacturer’s product. Three systematic reviews were also evaluated. Once again, there was a failure to consider meeting the standards of normal science in presenting modeled claims for cost-effectiveness.